(3GdeKdKs - (3CHh Ydj Hf CMeO Hf GdeSJfjQ, bWQH,J (B206 (3g` s
(3ChdgG (B:s
(3MOKfG CHh GdWjH eMeO Hf LHQGFjd bGd (B: (3bQCJ gPG GdcJGH Ydi CHj GdMSf CMeO Hf GdaVd jJUQa Ydi KdGKI ChLg (B: (3GdfhY GdChd efg GdZeQ hGdZeQ hGdZeQ s
(3BNQgG (B:s
(3ef GdfhY Gdehai KdGKjf (B" (3hGdUd HGdcSQMjI UaQGA Jchf ai GdQed hGdUd HGdaGM UhJ GdMOjO HYVg ahb HYV Je GdcJGH s
(3GdNW ajg HYV edGeM GdNW GdeZQHi HgG CKGQ WeS hfbYs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B198 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs